2020
DOI: 10.3390/ma13133029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Structural and Spectroscopic Properties of Iron(II)-Octacyanoniobate(IV) Crystalline Film Obtained by Ion-Exchange Synthesis

Abstract: Over recent years, investigations of coordination polymer thin films have been initiated due to their unique properties, which are expected to be strongly enhanced in the thin film form. In this work, a crystalline [FeII(H2O)2]2[NbIV(CN)8]∙4H2O (1) film on a transparent Nafion membrane was obtained, for the first time, via ion-exchange synthesis. The proper film formation and its composition was confirmed with the use of energy dispersive X-ray spectroscopy and infrared spectroscopy, as well as in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The films microstructure compares favorably to that of the films obtained from related CN‐bridged networks. The films obtained from suspension show smaller grain size and better surface evenness in comparison to PBAs obtained by electrochemical deposition, [ 24 ] the Fe II ‐Nb IV based network obtained by ion‐exchange [ 41 ] and the Fe II ‐Pt II Hoffman‐type network obtained by pulsed laser evaporation. [ 38 ] The morphology of the films obtained by sequential growth is similar to that of the films obtained by the same method from PBAs [ 33 ] and Hoffman‐type networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The films microstructure compares favorably to that of the films obtained from related CN‐bridged networks. The films obtained from suspension show smaller grain size and better surface evenness in comparison to PBAs obtained by electrochemical deposition, [ 24 ] the Fe II ‐Nb IV based network obtained by ion‐exchange [ 41 ] and the Fe II ‐Pt II Hoffman‐type network obtained by pulsed laser evaporation. [ 38 ] The morphology of the films obtained by sequential growth is similar to that of the films obtained by the same method from PBAs [ 33 ] and Hoffman‐type networks.…”
Section: Resultsmentioning
confidence: 99%
“…Deposition of hybrid organic-inorganic CN-bridged networks, apart from isolated reports, is a practically unexplored area. [38][39][40][41] Numerous earlier studies on other molecular magnets, particularly those devoted to anchoring SMMs on surfaces, have shown that magnetic properties are easily influenced by both reduction of the particle size as well as interface interactions with the substrate. [42][43][44] Therefore, in order to employ solvatomagnetic properties in the construction of chemo-sensitive switches it is essential to investigate if the properties of the bulk material are retained in thin films.…”
Section: Introductionmentioning
confidence: 99%